Untapped endophytic colonization and plant growth-promoting potential of the genus Novosphingobium to optimize rice cultivation - Chakrapong Rangjaroen (2018)
© 2017, Japanese Society of Microbial Ecology. All rights reserved. With the aim of searching for potent diazotrophic bacteria that are free of public health concerns and optimize rice cultivation, the endophytic colonization and plant growth-promoting activities of some endophytic diazotrophic bacteria isolated from rice were evaluated. Among these bacteria, the emerging diazotrophic strains of the genus Novosphingobium effectively associated with rice plant interiors and consequently promoted the growth of rice, even with the lack of a nitrogen source. These results suggest that diazotrophic Novosphingobium is an alternative microbial resource for further development as a safe biological enhancer in the optimization of organic rice cultivation.